Case Report: Abdominal Wall Abscess as First Clinical Sign of Jejunal Perforation After Blunt Abdominal Trauma - M. Martínez-López; M. Verdaguer-Tremolosa; V. Rodrigues-Gonçalves; M. P. Martínez-López; M. López-Cano (Journal of Abdominal Wall Surgery)
AimTo discuss extended retrorectal abscess secondary to blunt abdominal trauma as a cause of abdominal wall (AW) infection and impairment.MethodsAccording to the CARE checklist, we describe a rare case of blunt abdominal trauma with late diagnosis of jejunal perforation with an abscess that extensively dissected the retromuscular space.ResultsA 65 years-old female patient experienced multiple traumas after a traffic collision. Ten days after admission, the patient presented with swelling in the right abdomen. CT scan showed localised pneumoperitoneum and extensive collection affecting the right retrorectal space, reaching the ribs and preperitoneal space. Urgent laparotomy was performed and jejunal perforation with biliary peritonitis and extraperitoneal extension with dissection of the right retrorectal space were found. Intestinal resection with anastomosis was then performed. Exhaustive lavage of the cavity and retromuscular space with debridement of the necrotic posterior rectus lamina was required. Retrorectal drainage was placed. Primary closure of the aponeurosis was achieved using a small-bites technique with a slowly absorbable monofilament suture. Due to the weakness of the abdominal wall, an absorbable biosynthetic mesh impregnated with gentamicin was placed onlay. Negative pressure therapy was applied to the closed wound. Patient received antibiotics and CTs showed favourable evolution. No infectious complications or incisional hernia were reported after 12 months of follow-up.ConclusionNo cases of blunt trauma causing extensive AW infection have been reported in the literature. Whilst rare, this should be considered in traumatic patients. Our experience shows that they can be managed with surgical drainage and absorbable meshes can be considered in cases of fascial loss.